(untitled) (Research, Society and Development, 2022)
The contribution of the information provided here is in correlation with the elaboration of the Master’s Project in Regional Development at the Federal University of Amapá-UNIFAP. The objective is to weave a dialogue of conceptual information on biodiversity being developed by several authors, as well as to understand the local development of the community of São Francisco do Iratapurú/AP through the use of access to the benefit sharing of associated traditional knowledge. The methodology adopted to the study is to explain the phenomenon of constitutive actions of the public spheres in local development. Thus, this work is structured in three sub-topics, in which initially the first consists of describing the trajectory of biodiversity in the world, Brazil and Amapá. The second sub-topic is the approach to local development and access to biodiversity of existing natural resources in the Community of São Francisco of the Iratapurú River/AP and how access to this local benefit is given. It consists in emphasizing a brief description of the real benefits that remain for the local community of the Extractive Reserve of Sustainable Development of the Iratapurú River. This scientific approach is justified in providing access to information inherent to the local development of the community so that all legal support provided in the Federal Constitution will be used as a strengthening benefit for the entire locality of Iratapurú.